American Dolorologies Pain, Sentimentalism, Biopolitics - Strick, Simon (SUNY Press Open Access, 2014)
Offers a critical history of the role of pain, suffering, and compassion in democratic culture.American Dolorologies presents a theoretically sophisticated intervention into contemporary equations of subjectivity with trauma. Simon Strick argues against a universalism of pain and instead foregrounds the intimate relations of bodily affect with racial and gender politics. In concise and original readings of medical debates, abolitionist photography, Enlightenment philosophy, and contemporary representations of torture, Strick shows the crucial function that evocations of "bodies in pain" serve in the politicization of differences. This book provides a historical contextualization of contemporary ideas of suffering, sympathy, and compassion, thus establishing an embodied genealogy of the pain that is at the heart of American democratic sentiment.Simon Strick is Postdoctoral Researcher at the Center for Literary and Cultural Research Berlin in Germany.